2002
DOI: 10.1136/fn.86.3.f190
|View full text |Cite
|
Sign up to set email alerts
|

Can transcutaneous bilirubinometry reduce the need for blood tests in jaundiced full term babies?

Abstract: Background: Previous studies have suggested that transcutaneous bilirubinometry (TcB) may provide a useful method for screening for significant jaundice, thereby reducing unnecessary blood tests. These studies have not allowed an estimation of the magnitude of such a benefit. Objectives: To evaluate the accuracy of TcB as a method of determining the need for serum bilirubin (SBR) measurements in full term babies and to quantify the magnitude of any benefit. Subjects: Babies born at more than 34 weeks gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 8 publications
1
32
1
1
Order By: Relevance
“…These instruments have been shown to give results that correlate well with serum bilirubin values, but exhibit large scattering [1]. Consequently, with the application of non-invasive bilirubinometers, the number of serum measurements could be reduced and painful heel pricks avoided but not completely abolished [5,15]. Warnings have been published for the use of bilirubinometers in newborns with dark and yellow skin and in bright sunlight [23].…”
Section: Introductionmentioning
confidence: 99%
“…These instruments have been shown to give results that correlate well with serum bilirubin values, but exhibit large scattering [1]. Consequently, with the application of non-invasive bilirubinometers, the number of serum measurements could be reduced and painful heel pricks avoided but not completely abolished [5,15]. Warnings have been published for the use of bilirubinometers in newborns with dark and yellow skin and in bright sunlight [23].…”
Section: Introductionmentioning
confidence: 99%
“…Others have questioned the accuracy of transcutaneous bilirubin (TcB) measurements, particularly in neonates with relatively high TSB. [12][13][14][15][16] The majority of studies of TcB have focused on hospitalized neonates prior to peak TSB values. If reliable TcB results could be demonstrated following discharge, when higher TSB values would be anticipated, this rapid, noninvasive, pointof-care technique would be attractive to parents and useful for providers who are implementing the AAP guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In the former study, the researchers have mentioned that TcB is as accurate as SBR and can replace it. 7 Karon et al showed that TcB is a sensitive but nonspecific method for predicting the risk of neonatal icterus.…”
Section: Discussionmentioning
confidence: 99%